Economies of scale in Peru’s water and sanitation sector - Mercadier, Augusto Carlos (2016)
This paper quantifies economies of scale in Peru’s water and sanitation (W&S) sector based on a five-year panel (2006–2010) that examines 39 water services providers. Our findings highlight the lack of economies of scale in the Peruvian W&S sector as a whole. Cost savings are possible through water volume increases (Economies of Production Density) and a higher provision density (Economies of Customer Density), but not via an increase in the number of served municipalities (overall Economies of Scale). Some agglomerations are possible, yielding cost reductions of up to 9 %.